The Urgency of Legal Protection Reform for Workers’ Mental Health: A Comparative Study of Indonesia and Singapore - Almufarrida, Salsabila; Malie, Adi Muliawansyah (SIGn Jurnal Hukum, 2025)
The current global paradigm shift in the employment sector no longer focuses exclusively on physical safety. Instead, this focus has expanded to the urgency of protecting workers’ psychological well-being. Unfortunately, the issue of worker mental health in Indonesia remains marginalized within the labor law framework. This research aims to critically analyze the technical normative vacuum within national regulation. Furthermore, this study aims to formulate an ideal regulatory model by adopting best practices from Singapore. This research employs a doctrinal legal research method, drawing on statutory, conceptual, and comparative approaches. This study examines in depth the legal architectural gaps between the two countries. The results reveal crucial facts regarding Article 35 section (3) of Law Number 13 of 2003. Although the article mandates protection of mental health, the absence of specific implementing regulations renders the norm unenforceable. This condition differs from Singapore, which possesses the WSHA 2006 and integrated Tripartite Advisory technical guidelines. This disparity creates structural vulnerability for Indonesian workers against psychosocial hazards. These hazards include extreme work stress and intimidation, exacerbated by the lack of standardized early-detection instruments. As a prescriptive solution, this research recommends the issuance of a specific Ministerial Regulation on Mental Health Protection at the Workplace. This regulation must mandate psychosocial risk assessment and require access to EAP. This reform is urgently needed to shift the protection paradigm from a voluntary, reactive approach to a mandatory, preventive one. This is necessary to guarantee workers’ fundamental rights to a healthy and dignified working environment.